The Main Character’s False Impression in Zappia’s Made You Up - Ningsih, Cahya (English Literature Study Program, 2022)
Delusions deeply held beliefs or false impressions, even though they contradict reality and what is generally thought to be true. This study used the theory of literary criticism because literary criticism focused on literary works. The researcher analyzed the delusional disorder experienced by Alex using literary criticism theory with a psychological approach. This study aimed to examine Alex's mental disorder in the book Made You Up using delusional theory within the scope of Literary Psychology. The researcher tried to find the dominant form of delusion experienced by the character and how the delusion affected personality development. The data were taken from the memoir Made You Up by Francesca Zappia in the form of sentences, conversations, and statements. The data were analyzed using the delusional theory by Leeser and O'Donohue. This study aimed to examine as well as distinguish several types of delusions that occured in the book. Therefore, this study examined sequence by sequence occured in the book. In this study, the results showed that Alex's delusions included threatening feelings, and having beliefs that were considered subjective. Then how did delusions affect Alex's personality development where he quickly became emotional, felt excessively anxious, and became depressed because he locked himself up in his room a lot. Some delusions were quick and immediate, while others were more enduring and persisting over a long period.